Merck : from a pharmacy to a global coporation 1668-2018 - Burhop, Carsten; Kißener, Michael; Schäfer, Hermann (C.H. Beck, 2018)
Merck is the world's oldest pharmaceutical and chemical company. It developed from a Darmstädter pharmacy, for which Friedrich Jacob Merck received the privilege in 1668, to a global corporation. This book tells its 350-year history for the first time in its entirety, on the basis of all available sources as well as the latest business history research. For a long time, family-owned companies were considered a phase-out model. The future seemed to belong to the corporation with an anonymous shareholder structure. But there are numerous successful counterexamples, such as Bosch, C & A, Bertelsmann or Merck. How did the family manage to hold the company for over 13 generations, through all political upheavals and historical crises, making it a global leader in science and technology? Four distinguished company historians tell the fascinating story of Merck between 1668 and 2018 and embed it in the eventful course of world history.